Peranan Unit Jibom Korps Brimob Polri dalam Menangani Tindak Pidana Terorisme Berupa Penggunaan Bom dan Bahan Peledak - Rizki Aulia Hidayat; Hernawati RAS (Jurnal Hukum Lex Generalis, 2023)
The criminal act of terrorism was formulated as a draft act of violence to cause fear in the crowd. So the use of bombs and explosives is an effective means of terrorism. This is a challenge for the Jibom Unit of the Polri Brimob Corps which was formed based on the mandate of the Police Regulation Number 11 of 2010 concerning the Handling Of Bomb Defusing. Bomb defusing must be carried out in an integrated manner and bomb defusing regulations must be coordinated between relevant parties. Technically, Perkapolri Number 11 of 2010 concerning The Handling of Bomb Defusing must be revised, the revision is related to the system and procedures for handling and defusing bombs in more detail.